Sensor fault diagnosis and processing for a two-speed AMT for pure electric vehicles. (3rd May 2016) - Hu, Jian-Jun; Li, Jian-Zhang; Liu, Yu-Hang; Xue, Mei; Yi, Zhang
Abstract: In shifting process for the two-speed AMT (automated manual transmission) in this paper, the position of synchronizer sleeve is reflected by output signal of an angular displacement sensor, therefore, the normal operation of the sensor is the key to complete shifting accurately and reliably. To improve the fault-tolerant ability of two-speed AMT for electric vehicles, the operation principle of the shifting actuator and the shifting process of the two-speed AMT are analyzed. A signal revised strategy and a vehicle failure mode are proposed for the sensor signal drift and sensor fault respectively. A test bed based on dSPACE real time simulation was set up for the two-speed AMT and the sensor fault diagnosis and processing strategy was verified by experiment. The experiment results indicate that the proposed strategy can be achieved under the simulation of sensor signal drift and sensor fault, improving the reliability of the AMT.